Uji Aktivitas Antibakteri Hasil Fermentasi Bakteri Endofit Umbi Talas (Colocasia esculenta L.) terhadap Bakteri: MINI REVIEW - Azka, Andi Aulia Urrahman; Kartika, Rudi; Jofri, Dirga Hosea Seventeen; Rizkirullah, Muhammad Adhitya; Kurniawan, Andi; Aswat, Muhammad Raihan (PROSIDING SEMINAR KIMIA, 2025)
Antibacterial agents are substances used to eliminate microorganisms, especially those harmful to humans. These antibacterial compounds can be directly extracted from plants, where the extracts contain secondary metabolite compounds with antibacterial activity. The antibacterial testing is conducted on gram-positive bacteria, such as Propionibacterium, Staphylococcus, and others. The research method employed is a literature review of 10 national and international articles published within the last 10 years. The cited articles focus on studies of plants with potential as antibacterial agents against several gram-positive bacteria, including the extraction solvents used, the metabolite compounds present in the extracts, and their effectiveness based on the inhibition zone diameter and/or minimum inhibitory concentration using the disc diffusion method. Keywords : Antibacterial, Diffusion Discs, Gram Positive, Secondary Metabolites